Dehydrated hereditary stomatocytosis: clinical perspectives - Frederiksen, Henrik (J Blood Med, 2019)
Dehydrated hereditary stomatocytosis (DHSt) is a nonimmune congenital hemolytic disorder characterized by red blood cell (RBC) dehydration and lysis. It has been a recognized diagnostic entity for almost 50 years, and autosomal dominant inheritance has long been suspected, but it was not until 2011 that the first genetic alterations were identified. The current study reviews 73 articles published during 1971–2019 and focuses on clinical perspectives of the disease. All but one of the published clinical data in DHSt were either single case reports or case series. From these, it can be seen that patients with DHSt often have fully or partially compensated hemolysis with few symptoms. Despite this, iron overload is an almost universal finding even in patients without or with only sporadic blood transfusions, and this may lead to organ dysfunction. Other severe complications, such as thrombosis and perinatal fluid effusions unrelated to fetal hemoglobin concentration, may also occur. No specific treatment for symptomatic hemolysis exists, and splenectomy should be avoided as it seems to aggravate the risk of thrombosis. Recently, treatment with senicapoc has shown activity against RBC dehydration in vitro; however, it is not known if this translates into relevant clinical effects. In conclusion, despite recent advances in the understanding of pathophysiology in DHSt, options for clinical management have not improved. Entering data into international registries has the potential to fill gaps in knowledge and eventually care of these rare patients.